The determinants of cost estimators’ performance in construction projects: an exploration of organisational control, contingency and task technology fit theories - Mohammad Waffy, Fazil (2024)
Ensuring the excellent performance of cost estimators is paramount for project success, especially within complex industries such as construction. However, many organisations fail to recognise the significance of implementing robust cost estimation practices to enhance the performance of these estimators. While previous studies have identified various factors influencing cost estimation performance, such as input, behaviour, and output controls, as well as task characteristics and estimation methods, the causal relationships between these factors and performance remain largely unexplored, particularly in the context of varying project complexities. This study aims to address these gaps by pursuing three objectives: (1) examining the impact of organisational control on cost estimation performance, specifically focusing on task performance, contextual performance, and counterproductive work behaviour, (2) assessing how project complexity moderates the relationship between organisational control and cost estimator performance, and (3) evaluating the impact of task-technology fit on cost estimator performance.. Using internet-based and drop-off surveys, we distributed a total of 489 questionnaires to specialised staff with cost estimation expertise in Malaysian construction firms, achieving response rates of 31.69% and 40.95%, respectively. After data screening, 152 questionnaires were utilised for subsequent analysis. Employing the SmartPLS 4 package and partial least squares structural equation modelling, our study tested 25 hypotheses, revealing several significant positive relationships, including those between input control and contextual performance, output control and task performance, output control and contextual performance, and behaviour control and counterproductive work behaviour. Our findings suggest opportunities for improvement in cost estimator performance through managerial implementation of input and output control while highlighting potential drawbacks associated with an emphasis on behaviour control. Additionally, adaptation to advanced cost estimation methods through technology can enhance contextual performance by improving compatibility between task and method characteristics. Regarding the moderating effect of project complexity, our results indicate significant moderation between various controls and cost estimator performance. This research carries essential implications for project managers aiming to enhance cost estimator performance in construction projects. It emphasises the complexity of individual performance improvement, highlighting the importance of not only task performance but also contextual performances and mitigating counterproductive work behaviour through the managerial implementation of various organisational controls. Furthermore, managers should consider project complexity when implementing organisational control for cost estimators in Malaysian construction projects, as it influences the impact of controls on cost estimator performance. Recognising the determinants of cost estimator performance from management, technology, and project perspectives can reduce the probability of cost overrun in Malaysian construction projects and effectively increase both economic and social benefits to Malaysia.